2014
DOI: 10.1590/s0103-90162014000100001
|View full text |Cite
|
Sign up to set email alerts
|

Process-based simple model for simulating sugarcane growth and production

Abstract: Dynamic simulation models can increase research effi ciency and improve risk management of agriculture. Crop models are still little used for sugarcane (Saccharum spp.) because the lack of understanding of their capabilities and limitations, lack of experience in calibrating them, diffi culties in evaluating and using models, and a general lack of model credibility. This paper describes the biophysics and shows a statistical evaluation of a simple sugarcane processbased model coupled with a routine for model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 36 publications
3
22
0
5
Order By: Relevance
“…The quantitative understanding of the influence of straw on the water availability of soil, the evaporation of soil water, and the transpiration of sugarcane crop can aid growers on making decision. This knowledge could be useful to be included in process based crop models (Marin and Jones, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative understanding of the influence of straw on the water availability of soil, the evaporation of soil water, and the transpiration of sugarcane crop can aid growers on making decision. This knowledge could be useful to be included in process based crop models (Marin and Jones, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the dry matter productivity simulated by the model also showed higher errors for ratoon crop, although most of the results are within the acceptable error (± 20%). Singels et al (2008), Marin et al (2011), Marin and Jones (2014) reported high variations in the estimate of this parameter in the modeling. Although satisfactory, results show a slight deficiency in the fresh and dry matter yield simulation model in ratoon crop and that can still be adjusted.…”
Section: Evaluation Of the Dssat/canegro Model Growth Variables Analysesmentioning
confidence: 98%
“…Dynamic crop growth models are tools used to assist in this planning. They allow greater understanding of the crop and its behavior in different management scenarios and climate, assisting in decision making (Thorp et al, 2008;Marin and Jones, 2014;Carvalho et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the solar radiation balance in the plant canopy in these different agricultural management is fundamental to understanding the growth and development processes (Sinclair & Muchow, 1999;Ferreira Junior et al, 2014b;Wang et al, 2015) and the application of models that use components of this balance as input variable ( Liu & Bull, 2001;Marin & Jones, 2014). Solar radiation intercepted (or absorbed) by the plant canopy is the most important component for growth analysis, but to estimate this radiation, it is necessary to know the leaf area index (LAI) and the extinction coefficient (k) (Silva & Costa, 2012).…”
Section: Introductionmentioning
confidence: 99%